Review on the effects of occupational therapy intervention in improving handwriting skills among preschool children - Masne Kadar,; Chai, Siaw Chui; Geoh, Mei Kei; Nor Afifi Razaob@Razab,; Farahiyah Wan Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The development of writing ability is not only important in building a child’s self-esteem, but also essential for academic success in school. Handwriting is an important skill that could affect students’ performance in most academic areas. This study aimed to review the effect of occupational therapy intervention in improving handwriting skills among preschool children. Relevant studies were systematically searched by using standardized keywords across three databases. The initial search identified 1,386 references. Of these studies, there were five quantitative studies that met the inclusion criteria and were methodologically appraised using the McMaster Critical Review Form–Quantitative Studies. All studies reported that preschool children with or without disabilities showed significant improvements in handwriting skills after receiving occupational therapy intervention. One study involved collaboration between teachers and occupational therapists in implementing intervention program to preschool students. Collaboration between teachers and occupational therapists was able to provide teachers with tools and skills that they can use to help students, with or without direct presence of occupational therapists. Overall, findings of this review indicated that preschool children could gain improvement in handwriting skills regardless of their conditions after receiving occupational therapy intervention programs.